LEAP Bozori: Kichik va O'rta biznes Korxonalari listingi uchun yangi platforma - Sherzod Botirjonov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides a concise overview of the LEAP Market introduced by Bursa Malaysia. It explores how this platform offers SMEs alternative fundraising opportunities with reduced regulatory requirements. Through comparative analysis with similar markets, it delves into the unique advantages and challenges of the LEAP Market. Additionally, it examines the market‟s impact on SME development, emphasizing its role in fostering entrepreneurship and innovation in Malaysia.